(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
When designing and setting up an electric power station, we must take into consideration the type of loads, load of future expansions and also study the effect of ambient conditions especially temperatures so that the power station is able to feed those loads,thus making it more stable ,so in this paper we study the effect of environment condition, especially the temperature degree , so if any increase or decrease in temp degree its mean increase in electric loads, therefore we need to increase the electric power generated from power station to match the incremental in the load .Therefore we design control devise depending on “Arduino technique” to control the number of units generators in power station that must work and connected to network to share the remain power unit with electric power generated when an increase or decrease in temperature degree to remain the electric power station with more stability in work.